Durable renovation of monumental heritage through impressed current cathodic protection (ICCP) – Case study: The Yser Tower - Van Belleghem Bjorn; Soetens Tim (MATEC Web of Conferences, 2025)
Condition assessment of 65-year-old concrete slabs in the top part of the Yser Tower monument (Belgium) showed corrosion damage leading to a risk for spalling of concrete and aesthetic masonry and corresponding safety issues. In order to obtain a durable and effective, yet non-invasive protection of the steel in the concrete elements, impressed current cathodic protection (ICCP) was adopted as a repair strategy. A CP system with TiMMO ribbons embedded into the joints between the concrete slabs was designed and implemented, rendering the system completely invisible from the outside. Performance assessment by means of decay measurements confirmed an effective corrosion protection.